Hexabromocyclododecane in polystyrene packaging: A downside of recycling?. (May 2018) - Abdallah, Mohamed Abou-Elwafa; Sharkey, Martin; Berresheim, Harald; Harrad, Stuart
Abstract: While there are no regulatory fire safety obligations for polystyrene (PS) when used as packaging material, concerns exist that such packaging material may contain the flame retardant hexabromocyclododecane (HBCDD) as a result of uncontrolled recycling activities. To evaluate these concerns, we collected 50 samples of PS packaging materials from the UK and 20 from Ireland. HBCDD was detected in 63 (90%) of samples, with concentrations in 4 samples from Ireland exceeding the EU's low POP concentration limit (LPCL) of 0.1% above which articles may not be recycled. Moreover, 2 further samples contained HBCDD >0.01%. While our samples were obtained in the 12 month period prior to the March 2016 introduction of the EU's 0.01% concentration limit above which articles may not be placed on the market, our data suggest that continued monitoring is required to assess compliance with this limit value. Ratios of α vs. γ-HBCDD in our EPS packaging samples (average = 0.63) exceeded significantly (p = 0.025) those in EPS building insulation material samples (average = 0.24) reported previously for Ireland. This shift towards α-HBCDD in packaging EPS is consistent with the additional thermal processing experienced by recycled PS and suggests the source of HBCDD in PS packaging is recycled PS insulation foam. This is of concern owing to the higher bioavailability and lower metabolic clearance of α-HBCDD compared to the β- and γ-isomers. Highlights: HBCDD present in 90% of Irish and UK polystyrene packaging samples. Concentrations of ΣHBCDD range between <0.7 μg kg −1 to 0.59%. HBCDD concentrations in 6 samples would prevent them being placed on EU market. Source of HBCDD in polystyrene packaging is recycled insulation foam.